Knowledge mining for the differentiation pattern with respect to the productivity and trophic status of some selected lakes of Western Himalayas - Kumar, Rakesh; Jindal, Rajinder; Kulharia, Mahesh; Sharma, Amit Kumar; Thakur, Kushal; Brar, Bhavna; Mahajan, Danish; Sharma, Ankita; Kumar, Sunil; Sharma, Dixit (Frontiers in Environmental Science, 2023)
Present study deals with an account of Primary Productivity and trophic status of Rewalsar, Kuntbhyog and Prashar lakes of Western Himalaya .Seasonal variations in (GPP g C m–2 day–1), (NPP), Respiration (R) and NPP/R ratio have been studied and compared with hydrobiological factors. Among various factors temperature, light, nutrients and chlorophyll- a were accountable for high productivity. Nygaard’s trophic state indices were calculated. GPP showed positive relationship with water temperature, penetration of light, nitrate and with phosphate. Extensive range of compound index observed in Rewalsar Lake (12.00-20.00) and Kuntbhyog Lake (12.50-18.00) confirmed their eutrophic nature. Based on the trophic classification of waters and on the basis of productivity, Nygaard’s trophic state indices, and richness of nutrients, Rewalsar and Kuntbhyog lakes could be categorised as eutrophic, whereas Prashar Lake as oligo-eutorphic. Based on the presence, absence, freqency of appearance and abundance of different organisms recorded during present investigation, bioindicators of trophic status have been determined.